Investigation on the growth performances of selected probiotic supplemented tilapia (Oreochromis niloticus) and walking catfish (Clarias batrachus) fingerlings - Jahan, Tamanna; Ali , Md Ayub; Rahman, Tanvir (Fundamental and Applied Agriculture, 2016)
The importance of probiotics in nutrition and health of aquaculture species is widely recognized. The current study was conducted to evaluate the effects of two commercial probiotic supplemented diets on the growth performance of monosex tilapia, Oreochromis niloticus and walking catfish, Clarias batrachus fingerlings. A 4- week long feeding trial was conducted with eight 35 L capacity rectangular glass aquaria using 48 O. niloticus (13.34 ± 2.19 g) and 48 C. batrachus (13.26 ± 1.50 g). Two available commercial probiotics were added with commercial fish feed (starter 1) and introduced in aquaria twice-a-day at 3% body weight in three forms; feed +1% probiotic Eskalina, Eskayef (organic spirulina 100%) (D1), feed + 1% mixed bacterial probiotic BioFav Aqua, Novertis (D2), feed + 1:1 ratio mixture of probiotics 0.5% Eskalina + 0.5% Bio BioFav Aqua (D3) and feed without probiotic (D4) as control. Proximate composition of feed samples was examined. Morphometric measurements of experimental fish and water quality parameters were determined weekly. The results showed that net weight gain, percent weight gain, specific growth rate (SGR) and protein efficiency ratio (PER) were found higher in O. niloticus and C. batrachus fed with diet D3 and diet D1, respectively. On the other hand, control diet, D4 showed lower growth and feed efficiencies for both fishes compared to other diets. The percentage of survival was independent of treatments. Whole body protein, fat and ash contents were higher and moisture content was lower in both fish fed with diet D1 followed by D3, D2 and control. These results suggest that diets incorporated with probiotics may be used as regular feed in O. niloticus and C. batrachus culture for better feed efficiency and growth performance. Spirulina supplemented diet, D1 and mixture of spirulina + probiotic bacteria supplemented diet, D3 appear to be more adequate respectively for the commercial farming of C. batrachus and O. niloticus.